Analysis of The Effect of Compensation, Organizational Commitment, and Work Environment on Employee Performance - Happy Danni; Ahmad Alim Bachri (Journal of Social Science, 2021)
The purpose of this study is to find out and analyze the simultaneous and partial influence of compensation, organizational commitment, and work environment on employee performance at PT Sarana Daya Mandiri Banjarmasin. This research is explanatory research, which is a study that highlights between variables and tests the hypotheses that have been formulated. The type of research used is associative (causal relationship), which aims to know the relationship between two or more variables. The research sample was as many as 36 respondents who were employees at PT Sarana Daya Mandiri Banjarmasin. Data analysis techniques are used multiple linear regression analysis. The results showed that compensation, organizational commitment and work environment simultaneously and partially affect employee performance. This indicates that if these three factors increase, it will directly impact the improvement of employee performance. Based on these results, the research hypothesis is accepted.